2019
DOI: 10.1007/s10342-019-01221-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparing direct and indirect leaf area measurements for Scots pine and Norway spruce plantations in Sweden

Abstract: The area of foliage absorbing solar radiation is often expressed as leaf area index (LAI). In this study, specific leaf area (SLA), leaf area at tree level (LA) and LAI at stand level were measured on eight experimental plots of Norway spruce (Picea abies) and Scots pine (Pinus sylvestris), together with tree and stand measurements from biomass harvest. Both projected area and half total surface area were measured, and a model of the relationship between the units was constructed. SLA was larger for pine (61.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 47 publications
1
19
0
4
Order By: Relevance
“…The approach by Kirchner et al (2014) has been developed for spruce stands but only 34 of the 104 plots included in this study were pure spruce stands. The leaf area index (LAI) in spruce stands is often higher than in pine stands (Panferov et al, 2009;Goude et al, 2019). Zhang et al (2003) found generally higher vd values for stands with higher LAI values.…”
Section: Estimation Of Deposition Velocities For No 2 and Nhmentioning
confidence: 99%
“…The approach by Kirchner et al (2014) has been developed for spruce stands but only 34 of the 104 plots included in this study were pure spruce stands. The leaf area index (LAI) in spruce stands is often higher than in pine stands (Panferov et al, 2009;Goude et al, 2019). Zhang et al (2003) found generally higher vd values for stands with higher LAI values.…”
Section: Estimation Of Deposition Velocities For No 2 and Nhmentioning
confidence: 99%
“…Higher water demands due to higher leaf area or tree size can influence the way species respond to drought. In Scandinavian boreal forests, spruce tends to have a higher leaf area compared to pine of a given size, and commonly grows in stands reaching higher leaf area index (LAI; Cienciala et al, 1997;Goude et al, 2019). Spruce, however, has lower stomatal conductance, as indicated by its lower Q DZ (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…leaf on or leaf off). Other studies where differences have occurred include Goude et al (2019) who concluded that both LAI-2000C and DHP techniques underestimated LAI (in two conifer species) compared to values derived from destructive biometric sampling, but that the digital HP method underestimated the 'true' values more than LAI200C method.…”
Section: Accepted Articlementioning
confidence: 99%